Determination of essential work of necking and tearing from a single tensile test - Korsunsky, A; Kim, K (Springer, 2005)
The energy (or work) characterizing the resistance of a structure to ductile fracture is important for many applications, from structural design to impact protection. Essential work of fracture (EWF) is one such measure traditionally associated with the specific energy, per unit cross sectional area, consumed during ductile fracture in a double edge notched tensile (DENT) specimen. This energy is referred to as 'essential' in order to distinguish it from the non-essential energy consumed on distributed plastic deformation accompanying fracture, but not required for material separation. The present article describes how the essential work of tearing can be determined from a single tensile test on an unnotched specimen. Tensile tests were performed on unnotched dog-bone (DB) tensile specimens carrying large numbers of markers, with continuous measurement of elongation between any two markers using a laser scanning extensometer. From such single test it is then possible to obtain multiple load-elongation curves for a large number of tensile specimens. This data is analyzed by separatng contributions to specimen elongation made by distributed (pre-softening) and localized (post-softening) plastic deformation. Essential and non-essential work of necking and tearing is determined for an aluminium alloy subjected to different heat treatments, and results compared with those obtained from conventional DENT tests.